Local Beliefs (Sanro) In Traditional Medicine Of The Bugis Tribe: A Study Of Culture-Based Physical Therapy - Naila resqiyah Naila (The Center for Language Development, Mataram State Islamic University., 2026)
Traditional Bugis medicine, particularly Sanro's role as a healer, has become an integral part of South Sulawesi's public health system. This research is a narrative literature review that synthesizes resources about culture-based physical therapy in Sanro practice, such as traditional massage (massage) and herbal application (pappasilan). Based on a reference analysis from anthropology and ethnomedicin journals, it was found that Sanro's physical therapy not only relies on manual techniques to deal with bone injuries, but is also embedded in Bugis cosmology such as the concept of balance and siri' (self-esteem). Although socioculturally effective, there are modernization challenges such as conflicts with biomedical demanding the integration of medical pluralism. These results highlight Sanro's potential for preservation through documentation and advanced clinical research, with implications for culture-based health policy in Indonesia.